The role of a simple and effective salicylidene derivative. Spectral broadening and performance improvement of PFO-based all-solution processed OLEDs. (December 2019) - Duarte, Luís Gustavo T.A.; Germino, José Carlos; Mendes, Rodrigo A.; Berbigier, Jônatas F.; Faleiros, Marcelo M.; Rodembusch, Fabiano S.; Atvars, Teresa D.Z.
Abstract: A new salicylidene derivative, the N, N′ -bis(salicylidene)-(2-(3′, 4′-diaminophenyl)benzothiazole (BTS), which exhibits an Excited State Intramolecular Proton Transfer (ESIPT) process was synthesised and successfully used as a guest in poly[9, 9-dioctylfluorenyl-2, 7-diyl] (PFO) for an all-solution-processed Organic Light-Emitting Diode (OLED). Compared to a similar diode with poly(9-vinylcarbazole) (PVK), the performance of the PFO:BTS diode was improved by 50-fold in terms of luminance, 20-fold in terms of current density and 14-fold in terms of current efficiency. We explain this higher performance to the significant enhancement of hole charge mobility, predicted by means of the Trap Charge Limited Current (TCLC) model. Moreover, because of the color combination and taking advantage of the PFO deep-blue emission and BTS emission involving the ESIPT process, white-light emission was produced in a single layer diode. Experimental data were supported theoretically using the Natural Transition Orbitals (NTO) of BTS and its vertical excitations energies by Density Functional Theory (DFT) at the PBE0/6–311++G(d, p) level. The diode rendered a current efficiency of 0.40 cd A −1 and luminance of 492 cd m −2 . Graphical abstract: Image 1 Highlights: Efficient salicylidene derivative improved PFO performance. Charge carrier mobility enhanced by using a simple and effective salicylidene. Low-cost salicylidene for organic electronics. All-solution-processed OLEDs for energy and matter economy. White-Light generation from host-guest composites.